From left to right, sitting: Langbord, his daughter Eleanor and his wife Becky. Dedication to Emma Goldman on the back. From Goldman-archive, nr.XXI
From left to right, sitting: Langbord, his daughter Eleanor and his wife Becky. Dedication to Emma Goldman on the back. From Goldman-archive, nr.XXI.